2011
DOI: 10.1007/s10706-011-9415-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of Natural Pozzolana and Lime for Stabilization of Cohesive Soils

Abstract: The present study investigates the use of natural pozzolana combined with lime for ground improvement applications. Laboratory tests were undertaken to study the effect of natural pozzolana, lime or a combination of both on the physical and the mechanical characteristics of cohesive soils. Natural pozzolana, lime and natural pozzolana-lime were added to two cohesive soils at ranges of 0-20 and 0-8%, respectively. Consistency, compaction, undrained traxial shear and unconfined compressive strength tests were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(45 citation statements)
references
References 27 publications
8
36
0
1
Order By: Relevance
“…However, when the curing factor was considered in such mixtures, the highest UCS values were obtained for the curing times of 7 and 28 days, at the intermediate (UCS = 578.28 kPa) and modified (UCS = 786.59 kPa) compaction efforts. Harichane et al (2011) reported that the reaction between soil and lime results in the formation of cementitious compounds that bind soil particles together and, that generally the UCS value increases with increasing curing time. According to Aldaood et al (2014), addition of lime to the soil generally improves its geotechnical properties and provokes an immediate exothermic reaction between the CaO present in lime and soil water, forming calcium hydroxide.…”
Section: /8mentioning
confidence: 99%
“…However, when the curing factor was considered in such mixtures, the highest UCS values were obtained for the curing times of 7 and 28 days, at the intermediate (UCS = 578.28 kPa) and modified (UCS = 786.59 kPa) compaction efforts. Harichane et al (2011) reported that the reaction between soil and lime results in the formation of cementitious compounds that bind soil particles together and, that generally the UCS value increases with increasing curing time. According to Aldaood et al (2014), addition of lime to the soil generally improves its geotechnical properties and provokes an immediate exothermic reaction between the CaO present in lime and soil water, forming calcium hydroxide.…”
Section: /8mentioning
confidence: 99%
“…The NP is found in abundance in areas of Beni-Saf located in the west of Algeria [20]. The NP was used in combination with L to improve the engineering properties of both GS and RS such as the shear strength, the plasticity and the UCS [10,11,21,22]. However, there is no investigation of the influence of CaSO 4 .2H 2 O on the stabilization of these soils.…”
Section: Department Of Matter Engineeringmentioning
confidence: 99%
“…This change caused by L reduces the plasticity index and the maximum dry density of the stabilized soil but increases their optimum moisture content [10]. At the later stage, the increase in the concentration of hydroxyl (OH -) from L raises the pH of the soil, and causes the dissolution of alumina and silica which interact with calcium ions to form cementing products such as calcium silicate hydrates (CSH) and calcium aluminate hydrates (CAH).…”
Section: Introductionmentioning
confidence: 99%
“…Then, it leads to flocculation due to the cation exchanges of which contributes to the increase of loess plasticity and workability. Furthermore, pozzolanic reactions induce the formation of cementitious compounds which lead to the increase of shear strength and stiffness of loess [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%